Exome Sequencing Identifies Abnormalities in Glycosylation and ANKRD36C in Patients with Immune-Mediated Thrombotic Thrombocytopenic Purpura - Basu, Malay Kumar; Massicano, Felipe; Yu, Lijia; Halkidis, Konstantine; Pillai, Vikram; Cao, Wenjing; Zheng, Liang; Zheng, X. Long (Thrombosis and Haemostasis, 2020)
Background Immune-mediated thrombotic thrombocytopenic purpura (iTTP) is a potentially fatal blood disorder, resulting from autoantibodies against ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13). However, the mechanism underlying anti-ADAMTS13 autoantibody formation is not known, nor it is known how genetic aberrations contribute to the pathogenesis of iTTP.Methods Here we performed whole exome sequencing (WES) of DNA samples from 40 adult patients with iTTP and 15 local healthy subjects with no history of iTTP and other hematological disorders.Results WES revealed variations in the genes involved in protein glycosylation, including O-linked glycosylation, to be a major pathway affected in patients with iTTP. Moreover, variations in the ANKRD gene family, particularly ANKRD36C and its paralogs, were also more prevalent in patients with iTTP than in the healthy controls. The ANKRD36 family of proteins have been implicated in inflammation. Mass spectrometry revealed a dramatic alternation in plasma glycoprotein profile in patients with iTTP compared with the healthy controls.Conclusion Altered glycosylation may affect the disease onset and progression in various ways: it may predispose patients to produce ADAMTS13 autoantibodies or affect their binding properties; it may also alter clearance kinetics of hemostatic and inflammatory proteins. Together, our findings provide novel insights into plausible mechanisms underlying the pathogenesis of iTTP.
Keywords: thrombotic thrombocytopenic purpura; glycosylation; mutations; pathogenesis; autoimmune diseases